The ‘New Year of the Woman’? Women, Violence, and Social Change Today - Manzin, Gregoria; Pezzotti, Barbara (Spunti e Ricerche, 2019)
This article works as a preamble to the volume dedicated to the theme of “Women and Violence in Italian Literature” by presenting an overview of the contemporary social and cultural scenario that can be used as a platform to reflect on the striking relevance and topicality of the literary works analysed in this special issue. It examines recent events, in Italy and on the international scene, which expose the dramatic escalation of an enduring cultural and social tension between two opposing forces. On the one hand, we live in a moment marked by a strong impetus for social change and an auspicious striving for more equitable gender representation. On the other, this wide-scale global momentum is contrasted by a resistance to shift the balance of power and to alter the status quo. This tension has expressed itself both at institutional and public level, as well as in the private realm. It has been publicly visible in recent episodes of gender-based civil conflict, dismissal and undermining of women in public positions, institutionalised discrimination, and violence against women. In an unprecedented manner, such episodes have received global attention, raised widespread outcry and generated powerful movements calling for social change while catalysing the impetus for women’s rights.